LITHOSPHERIC-SCALE GEODYNAMIC CONTEXT OF THE MESSINIAN SALINITY CRISIS - Jolivet L.; Augier R.; Robin C.; Suc J.-P.; Rouchy J.M. (My University, 2006)
Comparison between the tectonic and palaeogeographic evolution of the Mediterranean region from the Oligocene to the Present shows that the isolation of the Mediterranean region is a progressive process that started some 30–35 Ma ago. This comparison also emphasizes the importance of back-arc post-orogenic extension in forming the present-day tectonic setting and delaying the Messinian salinity crisis. It further shows that the Messinian salinity crisis occurred after the end of late-orogenic extension in the Alboran domain and the onset of a new stage of N–S compression in the westernmost Mediterranean. The crisis thus did not result from the slab retreat process that has instead probably favoured the connections between the Atlantic and Mediterranean waters during most of the Miocene. Conversely, without slab retreat and consequent extension, compression and crustal thickening would have instead closed the connections earlier and provoked an earlier salinity crisis. The slab retreat thus has probably delayed significantly the salinity crisis that is a logical consequence of the progressive isolation of the Mediterranean basin during convergence.
Keywords: Messinian; Cenozoic::Neogene::Miocene::Messinian; Кайнозой::Неоген::Миоцен::Мессинский